DC frequency modulation participated area control performance evaluation method - BA YU; WANG HAIXIA; LI WEIDONG; WANG YAN (2016)
The invention discloses a DC frequency modulation participated area control performance evaluation method. The DC frequency modulation participated area control performance evaluation method comprises the following steps of calculating a generalized area control error GCE; calculating a generalized control performance evaluation parameter GPS of a single area or multiple areas; calculating an integral control performance evaluation parameter DPS of the single area or the multiple areas; and performing coordinated evaluation by using the two parameters. The DC frequency modulation participated area control performance evaluation method is applicable for DC transmission participated frequency modulation. In the presence of the DC transmission participated frequency modulation, the frequency error may be affected by common adjustment of primary frequency modulation, secondary frequency modulation and DC frequency modulation. Therefore, separation of the responsible influence from the DC frequency modulation is r